Batf-dependent Th17 cells critically regulate IL-23 driven colitis-associated colon cancer. Issue 7 (2nd April 2015) - Punkenburg, Elise; Vogler, Tina; Büttner, Maike; Amann, Kerstin; Waldner, Max; Atreya, Raja; Abendroth, Benjamin; Mudter, Jonas; Merkel, Susanne; Gallmeier, Eike; Rose-John, Stefan; Neurath, Markus F; et al.
Abstract : Objectives: IBDs have an increased risk for development of colorectal cancer (CRC). Here, we aimed at the characterisation of the functional role of Th17-associated transcription factors in sporadic and colitis-associated colon cancer in vivo. Design: We used mice deficient or transgenic for the activating protein 1 family member basic leucine zipper transcription factor ATF-like (Batf) to evaluate the role of Th17 cells during sporadic and inflammation-induced colon carcinogenesis. We also studied the expression of Batf and RORγt in patients with IBD and CRC. Results: Batf but not retinoic acid-related orphan receptor γt (RORγt) expression was significantly increased together with interleukin (IL) 23 expression in UC but not in Crohn's disease (CD) tissue samples. In CRC also Batf but not RORγt expression was increased and its expression correlated with the IL-23 and IL-23 receptor (IL-23R) expression. Finally, Batf but not RORγt was coexpressed with IL-17a, IL-23R and IL-6 within CRC-infiltrating CD4 + T cells. Functional studies in mice revealed that Batf-dependent T cells are crucial regulators of sporadic and inflammation-induced CRC. Colitis-associated Batf −/− tumours lacked IL-17a + IL-23R + IL-6 + CD4 + T cells, hence displaying characteristics reminiscent of human CRC-infiltrating CD4 + T cells. Strikingly, Batf −/− tumours contained low IL-23 but high IL-17a expression levels. Tumour formation and intratumoral IL-23 expression could be restored by administration of Hyper-IL-6 consisting of IL-6 and soluble IL-6 receptor. Conclusions: Batf-dependent IL-23R + IL-6 + CD4 + Th17 cells critically control IL-23 driven colitis-associated tumour formation and the progression of sporadic colon tumours. Batf-dependent IL-23R + T cells represent a potential future therapeutic target limiting CRC progression.